STATUS NUTRISI SAPI PERANAKAN ONGOLR DI KECAMATAN BUMI AGUNG KABUPATEN LAMPUNG TIMUR - Repki Septori; Erwanto .; Rudy Sutrisna (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study was conducted in January 2014 in Bumi Agung District East Lampung Regency.This study aimed to determine the nutritional status of ongole cattle based on the feedstuff, nutrientcontent, and the management of feeding used by the ongole cattle breeder in Lampung Province.There were 15 breeders interviewed, came from three villages namely Margamulya (5 breeders),Donomulyo (5 breeders), and Lehan (5 breeders). This study used qualitative approach with surveymethod, then it was descriptively analyzed.The result of this study showed the feedstuff mostly in the form of pasture. Average dry matterconsumption was 7.32 kg/cow/day, even the dry matter need was 7.63 kg/cow/day, and averageprotein consumption was 0.76 kg/cow/day, even the protein need was 0.88 kg/cow/day. Can concludenutritional status of ongole cattle in Bumi Agung District East Lampung Regency has not therefare itfulfilled.